Analysis of Available Microcontroller Computing Resources for the Application of Some Cryptographic Hash Functions on Different Internet of Things Platforms - Dokic, Kristian; Mesic, Tomislav; Cobovic, Mirko (Springer Nature Switzerland AG, 2020)
In the last few years, there have been more and more security vulnerabilities in IoT devices. Some authors suggest the use of security algorithms and methods used on computers for protection, but in this paper, we propose that some hash encryption algorithms can be used in IoT application to provide integrity and authenticity of a message. It can be used when the risk of data misuse and the need for strong protection are low. Five different development boards are tested to prove that the proposed HMAC algorithm is not too computing-intensive. mbedTLS library has been used, and performance (speed) of boards have been measured with different secret key and payload size. We concluded that SHA256 and HMAC-SHA256 algorithms could be taken into account when deciding on the application of cryptography, primarily due to the ease of use and a low load of the microcontroller.
Analýza dostupných výpočetních zdrojů mikrokontroléru pro použití některých kryptografických hashovacích funkcí na různých platformách internetu věcí
Keywords: HMAC; SHA256; IoT; Arduino; mbedTLS; HMAC; SHA256; IoT; Arduino; mbedTLS